1993
DOI: 10.1037/0012-1649.29.6.989
|View full text |Cite
|
Sign up to set email alerts
|

Learning and emotional responsivity in cocaine-exposed infants.

Abstract: This study examined both instrumental responses and facial expressions during learning and extinction in a group of cocaine-exposed infants ages 4 to 8 months. Of the 72 infants studied, half were exposed to cocaine in utero and half served as matched controls. The groups were matched on maternal demographic characteristics and maternal use of other substances. Findings indicated that (a) infants exposed to cocaine had a significant decrease in mean birth weight and birth length; (b) cocaine-exposed infants sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 53 publications
5
53
2
Order By: Relevance
“…Specific deficits in a contingency learning task were also identified at 4 and 8 months in cocaine exposed human infants (Alessandri, Sullivan, Imaizumi, & Lewis, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…Specific deficits in a contingency learning task were also identified at 4 and 8 months in cocaine exposed human infants (Alessandri, Sullivan, Imaizumi, & Lewis, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…However, if examinations of at-risk populations are included, the number of extant studies becomes relatively larger. For example, children who have been exposed prenatally to cocaine demonstrate deficits in basic emotion expression such as delayed or idiosyncratic expression (e.g., Alessandri & Lewis, 1996a;Alessandri, Sullivan, Imaizumi, & Lewis, 1993;Bendersky, Alessandri, & Lewis, 1996). Other research has suggested that infants of mothers with high levels of depressive symptoms exhibit a lot of negative emotions and fewer positive emotions during learning tasks (e.g., Lundy, Field, & Pickens, 1996;Pickens & Field, 1993).…”
Section: Emotion Expression: Psychopathological Populationsmentioning
confidence: 99%
“…Struthers and Hansen (1992) found impaired recognition memory among cocaine and amphetamineexposed infants. Alessandri, Sullivan, Imaizumi, and Lewis (1993) reported impaired contingency learning, deficits in arousal, and low levels of emotional responsivity in cocaineexposed infants. found that infants exposed to cocaine were more likely to fail to start the habituation procedure.…”
mentioning
confidence: 99%